Microbial Community Composition Reveals Spatial Variation and Distinctive Core Microbiome of the Weaver Ant Oecophylla smaragdina in Malaysia - Chua, K.O.; Song, Sze Looi; Yong, Hoi Sen; See-Too, W.S.; Yin, W.F.; Chan, Kok Gan (Nature Publishing Group, 2018)
The weaver ant Oecophylla smaragdina is an aggressive predator of other arthropods and has been employed as a biological control agent against many insect pests in plantations. Despite playing important roles in pest management, information about the microbiota of O. smaragdina is limited. In this work, a number of O. smaragdina colonies (n = 12) from Malaysia had been studied on their microbiome profile using Illumina 16S rRNA gene amplicon sequencing. We characterized the core microbiota associated with these O. smaragdina and investigated variation between colonies from different environments. Across all 12 samples, 97.8% of the sequences were assigned to eight bacterial families and most communities were dominated by families Acetobacteraceae and Lactobacillaceae. Comparison among colonies revealed predominance of Acetobacteraceae in O. smaragdina from forest areas but reduced abundance was observed in colonies from urban areas. In addition, our findings also revealed distinctive community composition in O. smaragdina showing little taxonomic overlap with previously reported ant microbiota. In summary, our work provides information regarding microbiome of O. smaragdina which is essential for establishing healthy colonies. This study also forms the basis for further study on microbiome of O. smaragdina from other regions.